Characteristics of adherence of Actinobacillus actinomycetemcomitans to epithelial cells. - Meyer, D H (1994)
Actinobacillus actinomycetemcomitans smooth variants [SUNY 75(S), SUNY 465, 652] were investigated for their ability to adhere to KB epithelial cells. Both the type of medium (broth versus agar) and anaerobicity influenced adherence levels and cell surface characteristics. Optimal adherence was observed with all three strains after growth of the bacterial cells in broth under anaerobic conditions, a condition which was associated with extracellular microvesicles. Adherence of SUNY 75(S) also was correlated with extracellular amorphous material, whereas adherence of SUNY 465 was also associated with fimbriation which accompanied a smooth to rough phenotype shift. The relationship between adherence and extracellular vesicles, extracellular amorphous material, and fimbriation suggests that all of these components may function in A. actinomycetemcomitans adherence to epithelial cells. The phenotype shift observed in SUNY 465 cells is further evidence that A. actinomycetemcomitans SUNY 465 is predisposed to variant shifts which are associated with changes in adherence and invasion properties.